Facile synthesis of indolo[3,2-a]carbazoles via Pd-catalyzed twofold oxidative cyclization - Yang, Chao; Lin, Kai; Huang, Lan; Pan, Wei-dong; Liu, Sheng (Beilstein Journal of Organic Chemistry, 2016)
A rapid and efficient route has been developed for the synthesis of 9-methoxycarbonylindolo[3,2-a]carbazole derivatives. The key steps in this approach involved an aromatic amination and an oxidative biaryl coupling. Via the present route, indolo[3,2-a]carbazole derivatives are available in 3–4 steps based on commercially available starting materials.
Keywords: cyclization; indolo[3,2-a]carbazole; N-arylation; oxidative biaryl coupling; palladium catalysis